Keterampilan Budidaya Ikan Nila di Kolam Jaring Bambu (KJB) Sebagai Solusi kebutuhan Kelompok Tani ‘Abadi Tani’ Desa Peunia Kaway XVI - Lisa, Oviana; Lubis, Friyuanita; Aminah, Siti; Tanjung, Yulia Windi; Fuqara, Fantashir Awwal (Jurnal Pengabdian Agro and Marine Industry, 2025)
The community service activity with farmer group in Peunia Village is the first step in utilizing local natural resources. The community service members consist of farmer groups and students. In addition, Waterland has not been properly managed because of aquatic weeds. This situation gave rise to the idea of increasing the farmers' group's income through tilapia farming in bamboo net cages (KJB). The community service method applied an approach that involves a farmer group of 10 respondent. The results of the community service activities include education, assistance, and evaluation for the farmer group and students had constructed KJB cultivation is a semi-intensive technology. The evaluation increased the motivation and knowledge of the respondents, resulting in an average score of 3.5 (good) before the activity and 4.2 (very good). This KJB developed skills and reached business opportunities in the fisheries sector and the sustainable maintenance of the aquatic environment.